Attitudes of Farmers to Extension Trainings in Nigeria: Implications for Adoption of Improved Agricultural Technologies in Ogun State Southwest Region - Aromolaran, Adetayo Kazeem; Akerele, Dare; Oyekunle, Olalekan; Sotola, Abiodun Emmanuel; Komolafe, Taiwo Lateefat (Journal of Agricultural Sciences (Belgrade), 2017)
In Africa, the outcome of development research is enormous and its dissemination has been impactful, especially in Nigeria during the last few decades. This impact is observable in the adoption of innovation by farmers with the aim of transforming agricultural production. To enhance adoption, training of the farmers is required. However, the attitude of farmers towards training could influence their decision on the uptake of agricultural innovation. The purpose of this study was to evaluate whether the attitude of cassava farmers to training on selected improved agricultural technologies can substantially influence adoption of the technologies. A multistage sampling technique was used to select the sample size for this study. Data collected were analyzed using descriptive and inferential statistical tools. The findings showed that only a few (37.5%) of the farmers had a favourable attitude towards extension training with 64.25% of them having a low level of adoption of the technologies. While farmers’ attitude towards training exerted positive, howbeit minuscule influence on technology adoption, the perception of farmers about constraints to training on technologies had stronger influence. Factors with significant negative influence on adoption include, among others, diversification into non-farm occupations and age of farmers. Although the study admits that stimulating favourable attitude is important for innovation adoption, it maintains that substantial rates of adoption will only be achieved if constraints to training on agricultural technology adoption are addressed from farmers’ perspective, and agricultural production becomes attractive enough to hold farmers within the sector.